Computer vision using AWS AI services : learn best practices and how to build solutions using AWS managed computer vision services /: learn best practices and how to build solutions using AWS managed computer vision services. (2023) - Mullennex, Lauren; Bachmeier, Nate; Rao, Jay
No abstract available